2018
DOI: 10.12659/msm.906577
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Attenuates Chronic Intermittent Hypoxia-Induced Lung Injury by Inhibiting Inflammation and Oxidative Stress

Abstract: BackgroundIn the present study, we aimed to investigate the effects of sinomenine (SIN) on chronic intermittent hypoxia (CIH)- induced lung injury in rats, and to explore the underlying mechanisms.Material/MethodsTo perform the investigation, a CIH rat model was established. ELISA assay was applied to detect the level of inflammatory cytokines. Oxidative stress bio-markers (MDA, SOD, and CAT) were determined in lung tissues. In addition, the expression level of NADPH oxidase 2 (Nox2) was analyzed by Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Nowadays, a large body of studies has reported the pharmacological functions of SIN, including antinociception (Zhu et al, ), antihypersensitivity (Lagerstrom, ), neuroprotective activity (Gao et al, ), and even antitumor activity (Song et al, ). Because the clinical usage of C. Sinomenii in joint diseases, the anti‐inflammatory function of SIN in many types of diseases has also been revealed, such as asthma (Bao, Liu, Li, Men, & Zeng, ), sepsis (Jiang et al, ), Parkinson's disease (Qian et al, ), lung injury (Zhang, Rui, Wang, Lian, & Cai, ), and OA (Yang & Chen, ). Compared with nonsteroidal anti‐inflammatory drugs, SIN is more effective in amelioration of morning stiffness, painful joints, and erythrocyte sedimentation rate in patients with rheumatoid arthritis (Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a large body of studies has reported the pharmacological functions of SIN, including antinociception (Zhu et al, ), antihypersensitivity (Lagerstrom, ), neuroprotective activity (Gao et al, ), and even antitumor activity (Song et al, ). Because the clinical usage of C. Sinomenii in joint diseases, the anti‐inflammatory function of SIN in many types of diseases has also been revealed, such as asthma (Bao, Liu, Li, Men, & Zeng, ), sepsis (Jiang et al, ), Parkinson's disease (Qian et al, ), lung injury (Zhang, Rui, Wang, Lian, & Cai, ), and OA (Yang & Chen, ). Compared with nonsteroidal anti‐inflammatory drugs, SIN is more effective in amelioration of morning stiffness, painful joints, and erythrocyte sedimentation rate in patients with rheumatoid arthritis (Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, multiple studies have consistently reported that undiagnosed or inadequately treated OSA adversely affects asthma control, whereas continuous positive airway pressure as a treatment for OSA could attenuate the risk for poor asthma outcomes, partially due to the effects of intermittent hypoxia on airway inflammation and tissue remodeling [ 16 , 17 ]. Several other human and animal studies showed that OSA could shift the immune profile in patients with asthma from traditional eosinophilic or type 2 inflammation to neutrophilic or type 1 inflammation [ 16 , 18 , 19 ]. Additionally, real-world datasets showed an association between OSA and poor asthma control [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when the transcription, expression, and the secretion of pro-inflammatory cytokines were inhibited, the chronic pain could be successfully suppressed ( Martinez et al, 2008 ; Schaible 2014 ; Cook et al, 2018 ). Sinomenine was proved to have a powerful inhibitory effect on the secretion of various pro-inflammatory cytokines, such as IL-1β, TNF-α, and IL-6 in various diseases ( Zhao et al, 2013 ; Xiong et al, 2017 ; Kim et al, 2018 ; Zhang et al, 2018 ; Wang et al, 2020 ). It was reported that the concentration of IL-6 and IL-1β were significantly reduced in the serum of collagen-induced arthritis (CIA) rats treated with sinomenine, as well as their foot swelling, serological markers and arthritic scores, suggesting that sinomenine would be a potential drug for the treatment of RA inflammation ( Zhou et al, 2008 ).…”
Section: The Effects Of Sinomenine On Peripheral Immune Cellsmentioning
confidence: 99%